Building Independence and Learning Focus for Early Childhood Through Activity-Based Learning - Olivia Dwi Cahyani (SAHABAT: Jurnal Pendidikan Anak Usia Dini, 2026)
This research is driven by the significance of implementing activity-based learning in early childhood education to foster of children's independence, focus, and concentration, which are essential  foundations for learning readiness at the next level. However, learning practices in early childhood education often remain teacher-centered, so active participation of children has not developed optimally. Therefore, this study aims to analyze the role of activity-based learning in enhancing the independence, focus, and concentration of young children. This research uses a qualitative approach employing a library research design, with utilizing data derived from academic books, national and international scientific journals, and relevant documents related to early childhood learning and activity-based learning. Data was collected through documentation studies and analyzed using content analysis techniques to identify, review, and synthesize various findings from relevant literature. The results of the analysis indicate that activity-based learning encourages children's active engagement through exploration, direct experience, and interaction with teachers, peers, and the learning environment. Activities that are creatively and enjoyably designed not only enhance cognitive abilities but also build learning independence, decision-making skills, problem-solving abilities, as well as self-evaluation. In addition, diverse and interesting activities have been proven to improve children's focus and concentration, while simultaneously developing social-emotional skills such as cooperation, empathy, and self-confidence. The findings of this study provide practical implications for early childhood education teachers in designing learning activities that are more active, engaging, and child-centered, thereby supporting the development of independent character and children's learning readiness optimally from an early age.